Phenomenological Study: Smoking Behavior Among Women in Kab. Ogan Ilir - Merlina Azahra; Minarsi, Minarsi; Mutiara Dewi; Periti Sinta; Rosandra Rizky Julia (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Smoking behavior is a habit that has been going on for a long time in various cultures, especially in Indonesian society. This smoking behavior was previously considered an activity only carried out by men, but over time this trend has begun to develop among women. This research was conducted with the aim of exploring the meaning of smoking behavior for the life of a female smoker. The research method used is a qualitative phenomenological approach to understand the subjective experiences of female smokers. There were two female informants who were the subjects of this research. The research results show that smoking has a complex meaning in women's lives, often interpreted as a coping mechanism for dealing with stress and emotional conflict, both in romantic relationships and in the family environment. Even though smoking provides a sense of calm, this behavior has negative impacts on physical and psychological health, including the risk of heart disease, cancer, coughing, shortness of breath, insomnia and anxiety. It is hoped that this research can be used to design more effective preventive interventions.